Pengembangan Penilaian Kinerja pada Praktikum Larutan Penyangga untuk Menilai Keterampilan Proses Sains (KPS) Siswa SMA - Ainulhaq, Nurisa; Rahayu, Maya (Chemistry Education Department of Education and Teaching Faculty, 2023)
Abstract: Learning chemistry with a scientific approach not only views learning outcomes as final results, but students are directed to find various scientific activities in the form of processes and products. This study aims to develop a valid, reliable, and feasible performance appraisal to assess SPS in buffer solution practicum. The method used is development and validation. The results showed that the performance assessment was declared valid with a CVR value of 1.00, which is above the critical value of seven validators (0.622), and was reliable to score student SPS with a Cronbach alpha coefficient of 0.938 in a group of five people, 0.728 in a group of six people, and 0.674 in a group of eight people. The feasibility of performance appraisal in the buffer solution practicum to assess student SPS is feacable to use in groups with a maximum of five people for one observation so that rater consistency can be maintained, and 60% of raters state that performance appraisals are easy to use and administer.